الدراسة الأولية في المحكمة الجنائية الدولية - بارة, عصام (جامعة الوادي.University eloued, 2022)
دراسة الأولية هي إحدى الأنشطة الأساسية الثلاثة لمكتب المدعي العام للمحكمة الجنائية الدولية، إلى جانب التحقيق في الجرائم التي تدخل ضمن اختصاص المحكمة ومقاضاة مرتكبيها بموجب نظام روما الأساسي.ونظرا لأهمية هذه المرحلة المبكرة من الإجراءات، فمن خلالها يتم تقرير ما إذا كان يتعين فتح تحقيق من عدمه، جاءت هذه الورقة البحثية لتسليط الضوء على النظام القانوني الذي يحكم هذه الدراسة الأولية. The preliminary examination is one of the three core activities of the Office of the Prosecutor of the International Criminal Court, alongside investigating and prosecuting crimes under the Rome Statute. Given the importance of this early stage of the procedure, through which it is decided whether an investigation should be opened or not, this research paper came to shed light on the legal system that governs this preliminary examination.
Keywords: الدراسة الأولية؛المحكمة الجنائية الدولية؛ المدعي العام؛ الشروع في إجراء تحقيق; The preliminary examination; International Crprosecutor; to proceed with an investigation iminal Court